1977
DOI: 10.1071/pp9770821
|View full text |Cite
|
Sign up to set email alerts
|

Varietal Differences in Light Requirements for Germination of Celery (Apium graveolens L.) Seeds and the Effects of Thermal and Solute Stress

Abstract: Seed germination in one wild and two cultivated varieties of celery (Apium graveolens L.) was found to be light-dependent and mediated through the phytochrome system. Seeds of cv. Florida at 20°C were very sensitive to light and germination could be promoted by green safe light as well as by short far-red irradiation of brief duration, while seeds of wild celery did not respond to far-red and were less responsive to green safe light. At the optimal temperature, continuous irradiation with white light caused ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Seeds of Apium graveolens required light for germination, but this requirement was highly dependent on temperature, with germination in darkness decreasing as temperatures increased (Thomas et al . 1975; Pressman et al . 1977).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds of Apium graveolens required light for germination, but this requirement was highly dependent on temperature, with germination in darkness decreasing as temperatures increased (Thomas et al . 1975; Pressman et al . 1977).…”
Section: Discussionmentioning
confidence: 99%
“…1975; Jacobsen et al . 1976; Pressman et al . 1977, 1988; Biddington & Thomas 1979; Jacobsen & Pressman 1979; Coolbear et al .…”
Section: Introductionmentioning
confidence: 99%
“…Celery {Apium graveotens L.) is usually a biennial plant. In its first year the plant produces a rosette type shoot and in the second year, after exposure to low temperatures during the winter, it bolts and flowers (Pressman and Sachs 1985). However, 4 cultivars of celery obtained from Taiwan and Thailand are all annuals.…”
Section: Introductionmentioning
confidence: 99%
“…These showed that celery seeds generally require light for germination (Robinson 1954). Under low temperature conditions (10-15°C) some varieties germinate in the dark (Morinaga 1926, Taylor 1949, while others do not (Pressman et al 1977). Alternating temperatures can substitute for the requirement for light (Morinaga 1926(Morinaga , T-hompson 1974.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation